2000
DOI: 10.1097/00002030-200006160-00002
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic testing predicts virological response in successive protease inhibitor-based regimens

Abstract: This data confirm the usefulness of phenotypic testing in guiding antiretroviral therapy in heavily pretreated patients. The number of active drugs and the line of salvage therapy are independent predictors of virological response, regardless of HIV load and the length of antiretroviral exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…These data suggest that this mutation may be sufficiently contributing to AZT resistance with D67N, K70R, and T215F without requiring the mutations generally required to generate high-level AZT resistance (i.e., M41L, L210W, and T215Y) (12). While the changes in drug susceptibility in this study were small, recent studies have shown that even relatively modest susceptibility changes can correlate with clinical outcome (6,16). Two other significant mutational associations were seen with codon 69 mutations.…”
Section: Vol 45 2001mentioning
confidence: 56%
“…These data suggest that this mutation may be sufficiently contributing to AZT resistance with D67N, K70R, and T215F without requiring the mutations generally required to generate high-level AZT resistance (i.e., M41L, L210W, and T215Y) (12). While the changes in drug susceptibility in this study were small, recent studies have shown that even relatively modest susceptibility changes can correlate with clinical outcome (6,16). Two other significant mutational associations were seen with codon 69 mutations.…”
Section: Vol 45 2001mentioning
confidence: 56%
“…This recombinant virus can be tested in vitro against a variety of RT and PR inhibitors. Susceptibilities are reported as fold-changes in drug inhibiting concentrations (IC 50 ) as measured by comparing the mean inhibiting concentrations at which 50% replication is suppressed (IC 50 ) of the patients' HIV RT and PR genes to that of a reference HXB2 HIV strain Hanna and D'Aquila, 2001;Hirsch et al, 2003;Larder et al, 2001;Perez-Elias et al, 2000). One of the problems with phenotyping assays is that susceptibility can only be defined for one drug at a time, leaving important questions about drug interaction effects unanswered (Volberding and Lange, 2001).…”
Section: Phenotypic/fitness Assaysmentioning
confidence: 99%
“…The extent of antiretroviral resistance, measured prior to initiating new antiretroviral therapy, has been found to correlate with the likelihood of achieving viral suppression [8][9][10][11]. As the duration of follow-up in clinical trials has generally been 6 months or less [3][4][5][6], there are few or no data on the implications of antiretroviral resistance for clinical outcomes in HIV-1-infected individuals.…”
Section: Introductionmentioning
confidence: 99%